Religion and Reaction: The Secular Political Challenge to the Religious Right - Hansen, Susan B. (Rowman & Littlefield Publishers, 2011)
While the Religious Right has received considerable scholarly attention and media coverage in recent years, the story of the growing number of Secular Americans—those who identify themselves as atheists, agnostics, or as not having any religious ties—has yet to be told. In the first book devoted exclusively to Seculars, Susan B. Hansen argues that they are not only increasing in number and political involvement, but have devised strategies and alliances to counter the organization advantages of the Religious Right and its roots in church-based groups and the Republican party. Case studies of state and local battles over the issues of gay marriage, reproductive rights, and teaching evolution illustrate how Seculars have overcome organizational disadvantages to emerge as significant adversaries to the Religious Right. They have forged alliances with the media, the scientific community, minority groups, the Religious Left, and the Democratic Party to challenge the influence of traditional religious views on American politics and public policy.